2018
DOI: 10.1177/1360780418769677
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Methodological Challenges of Using Participant-Produced Digital Video Diaries in Antarctica

Abstract: Technological advancements have created new methods for conducting research. In this article, we explore the benefits and challenges of using participant-produced video diaries as a research method in a remote environment. Participant-produced video diaries provide rich ethnographic data of lived experiences. Moreover, video diaries allow data collection without researchers needing to be physically present, which facilitates research in remote locations. Therefore, we chose video diaries as one method of data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…women in leadership, sustainability). The content was delivered over 10-11 months pre-voyage as well as on board the ship to Antarctica (see Nash and Moore, 2018b).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…women in leadership, sustainability). The content was delivered over 10-11 months pre-voyage as well as on board the ship to Antarctica (see Nash and Moore, 2018b).…”
Section: Methodsmentioning
confidence: 99%
“…The study was conducted over a two-year period . Data for this article are drawn from post-program interviews and video diaries only (see Nash and Moore, 2018b).…”
Section: Methodsmentioning
confidence: 99%
“…For example, they have the advantages of providing rich data that 'vividly communicate the sheer physicality of embodied experiences'; to show as well as tell participants' experiences (Bates, 2013: 31;Cherrington and Watson, 2010). We have discussed the benefits and challenges of video diaries as a research method elsewhere (see Nash and Moore, 2018a). In this article, we reflect on the ethical challenges of using video diaries as a research method in our qualitative, longitudinal, mixed-methods study (which uses interviews, focus groups, video diaries and ethnography) of a leadership program for women in STEMM in Antarctica, a remote environment.…”
Section: Ethical Issues Associated With Video Diaries As a Research Mmentioning
confidence: 99%
“…The ethical issues associated with the research described in this article emerge from a mixedmethods study examining leadership for women in STEMM fields (see Nash and Moore, 2018a, 2018b, 2018cNash et al, 2017). This study focuses on a group of women from five countries in the Global North who self-identified as occupying and/or aspiring to a leadership position in STEMM and who were actively seeking to enhance their leadership capacities.…”
Section: Empirical Contextmentioning
confidence: 99%
See 1 more Smart Citation